2017
DOI: 10.1016/j.mee.2017.01.010
|View full text |Cite
|
Sign up to set email alerts
|

SiC polytypes and doping nature effects on electrical properties of ZnO-SiC Schottky diodes

Abstract: SiC polytypes and doping nature effects on electrical properties of ZnO-SiC Schottky diodes, (2017), doi:10.1016/j.mee.2017 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 38 publications
(38 reference statements)
0
6
0
Order By: Relevance
“…Table 1, summarize the results of the three fabricated solar cells. (Rebaoui et al, 2017). Therefore, contact resistance cause to increase in the value of series resistance which in turn decreases Voc and efficiency of the solar cell.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1, summarize the results of the three fabricated solar cells. (Rebaoui et al, 2017). Therefore, contact resistance cause to increase in the value of series resistance which in turn decreases Voc and efficiency of the solar cell.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, it can be seen from Figure 2 that, for all three devices, the forward bias I-V measurements deviate significantly from linearity with increasing voltage. This could be related to the effects of series resistance (Rebaoui et al, 2017). Moreover, from Figure 2 at the applied voltage of ±1V, it was observed that the values of diode rectification ratio (which can be determined by dividing the forward current (IF) to the reverse current (IR)) for PANI/(100) n-GaAs, PANI/(110) n-GaAs and PANI/(311)B n-GaAs devices are 5.35, 1.13 and 15.23, respectively as exhibited in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…The leakage current of the annealed diodes is one to two orders of magnitude lower than the as-grown diodes. The lower reverse current observed in the annealed diodes indicates that there is a reduction of the concentration of the defects which act as generationrecombination centers [16]. The annealing process decreases the concentration of major defects and consequently contributes to the decrease of the leakage current [17].…”
Section: Current-voltage Characteristics Of As-grown and Annealed Diodesmentioning
confidence: 97%
“…The higher ideality factor for the AZO/SiC/p-Si device indicates that thermionic emission is no longer the dominant transport mechanism. Other mechanisms such as barrier tunnelling and/or generation recombination in the space charge region, due to trap states, exist [28,78].…”
Section: Photoelectrical Propertiesmentioning
confidence: 99%
“…However, so far, little has been done on the combination of these materials. Some of the published works reported on ZnO/SiC heterojunctions grown directly either on 4H-SiC or 6H-SiC substrates [27][28][29][30], whilst in other works silicon was employed as the substrate of the heterojunction [31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%